2014
DOI: 10.1177/1076029614543139
|View full text |Cite
|
Sign up to set email alerts
|

Thromboprophylaxis and Incidence of Venous Thromboembolism in Patients With Hemophilia A or B Who Underwent High-Risk Orthopedic Surgeries

Abstract: Total hip replacement (THR) and total knee arthroplasty (TKA) carry a high risk of postoperative venous thromboembolism (VTE); therefore, anticoagulation prophylaxis is recommended in these patients. Unfortunately, there are no guidelines about VTE prophylaxis in patients with hemophilia who underwent these high-risk surgeries. To determine whether these patients have high risk of VTE, we conducted a retrospective study on patients with hemophilia who underwent elective THR/TKA at our institute from 2004 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…The true incidence of symptomatic venous thromboembolism (VTE) in patients with hemophilia undergoing such surgeries is still uncertain. The estimated incidence in previous retrospective studies ranged from 0% to 1% 10 - 12 , whereas the incidence of symptomatic VTE was as high as 4.3% in 1 prospective multicenter study 13 . In our study, the incidence of VTE was comparable between the hemophilia and control cohorts for both hip (0% versus 0.64%) and knee (1.15% versus 0.98%) procedures.…”
Section: Discussionmentioning
confidence: 91%
“…The true incidence of symptomatic venous thromboembolism (VTE) in patients with hemophilia undergoing such surgeries is still uncertain. The estimated incidence in previous retrospective studies ranged from 0% to 1% 10 - 12 , whereas the incidence of symptomatic VTE was as high as 4.3% in 1 prospective multicenter study 13 . In our study, the incidence of VTE was comparable between the hemophilia and control cohorts for both hip (0% versus 0.64%) and knee (1.15% versus 0.98%) procedures.…”
Section: Discussionmentioning
confidence: 91%
“…694 Although routine pharmacological thromboprophylaxis is controversial in haemophiliac patients undergoing major orthopaedic surgery, half of the comprehensive haemophilia centres in Europe reported using pharmacological antithrombotic prophylaxis after major orthopaedic surgery, 508 in contrast to 37% of respondents to a US survey 695 and 4% in a retrospective analysis of one US centre. 696 However, one centre reported that 82% of haemophiliacs received perioperative VTE prophylaxis after the year 2000 with no evidence of increased bleeding complications. 517 Individualised antithrombotic therapy, based on local clinical experience, guidelines for non-haemophilia patients and the patient's clinical characteristics is recommended.…”
Section: Haemophilia a And B Recommendationsmentioning
confidence: 99%
“…Therefore, all hemophilia centers will base their practices on the current state of knowledge and expert opinions until more valuable evidence is available. To the best of our knowledge, our series includes a larger number of hip/knee joint arthroplasties than the other reports 14,15 . The incidence of symptomatic VTE was 1 in 98 (1.02%) patients, which is lower than the incidence reported in the literature for patients without hemophilia undergoing the same surgical procedure in the absence of VTE prophylaxis 6 .…”
Section: Discussionmentioning
confidence: 85%
“…The average number of days of factor replacement was 16.78 (range, [14][15][16][17][18][19][20][21][22][23][24][25]. Serum mean FVIII level was 74.07%.…”
Section: Patient Characteristicsmentioning
confidence: 99%